APLIKASI MONITORING SPI - Firizza; Linda Fujiyanti; Sidhiq Andriyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Technological developments are very influential in various aspects, one of which is the development of information. The increasing use and search for information in the mass media, makes programmers try to make an application that will help users to get and carry out information seeking activities easily. Difficulties in conveying information and not yet computerized are the main problems for SPI. With the creation of an application that can manage the existing data on the SPI Polman Negeri Babel, it can be better organized and the integrity and security of the data can be guaranteed. This application is made using the waterfall model in order to produce a systematic and sequential system design. In addition, making application designs using Use Case Diagrams and application testing using the blackbox method. The results of making this SPI monitoring application provide convenience in displaying information, activities, and complaint features related to SPI.